Early dynamics of circulating tumor DNA predict clinical response to immune checkpoint inhibitors in metastatic renal cell carcinoma. (19th February 2022) - Koh, Yoko; Nakano, Kosuke; Katayama, Kotoe; Yamamichi, Gaku; Yumiba, Satoru; Tomiyama, Eisuke; Matsushita, Makoto; Hayashi, Yujiro; Yamamoto, Yoshiyuki; Kato, Taigo; Hatano, Koji; Kawashima, Atsunari; et al.
Abstract : Objectives: Detection of genomic alterations in circulating tumor deoxyribonucleic acid of peripheral blood can guide the selection of systemic therapy in cancer patients. The predictive significance of circulating tumor deoxyribonucleic acid in metastatic renal cell carcinoma remains unclear, especially for patients treated with immune checkpoint inhibitors. Methods: In this study, we collected plasma samples before and 1 month after commencing nivolumab monotherapy or nivolumab plus ipilimumab therapy from 14 metastatic renal cell carcinoma patients. We performed circulating tumor deoxyribonucleic acid genomic profiling in plasma cell‐free deoxyribonucleic acid by next‐generation sequencing using a commercially available pan‐cancer panel (Guardant360 CDx). Additionally, we also performed whole exome sequencing of tumor tissues and compared the concordance of genomic profiles with circulating tumor deoxyribonucleic acid. Results: Nine patients had circulating tumor deoxyribonucleic acid in pretreatment plasma samples with a total of 20 mutations (15 single nucleotide variants, three insertions/deletions, and two copy number amplification). VHL (30.0%) was the most frequently mutated gene, followed by TP53 (20.0%), and 45.0% of circulating tumor deoxyribonucleic acid mutations were concordant with somatic mutations in tumor tissues. Patients with decreasing circulating tumor deoxyribonucleic acid mutant allele frequency had better progression free survival when compared to those with increasing mutant allele frequency ( P = 0.0441). Conclusions: Our findings revealed that early circulating tumor deoxyribonucleic acid dynamics can serve as a predictive biomarker for response to immune checkpoint inhibitors in metastatic renal cell carcinoma patients.